2009
DOI: 10.1002/prot.22516
|View full text |Cite
|
Sign up to set email alerts
|

Challenging a paradigm: Theoretical calculations of the protonation state of the Cys25‐His159 catalytic diad in free papain

Abstract: A central mechanistic paradigm of cysteine proteases is that the His -Cys catalytic diad forms an ion-pair NH(+)/S(−) already in the catalytically active free enzyme. Most molecular modeling studies of cysteine proteases refer to this paradigm as their starting point. Nevertheless, several recent kinetics and X-ray crystallography studies of viral and bacterial cysteine proteases depart from the ion-pair mechanism, suggesting general base catalysis. We challenge the postulate of the ion-pair formation in free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…We recently demonstrated that in contrast to the paradigm, the His–Cys catalytic diad in free papain is fully protonated, NH(+)/SH 15. Our conclusion was supported by reproduction of the experimental p K a 's of His159 and the 1 H NMR chemical shifts of the CH ϵ proton of His159 16, 17…”
Section: Introductionmentioning
confidence: 52%
“…We recently demonstrated that in contrast to the paradigm, the His–Cys catalytic diad in free papain is fully protonated, NH(+)/SH 15. Our conclusion was supported by reproduction of the experimental p K a 's of His159 and the 1 H NMR chemical shifts of the CH ϵ proton of His159 16, 17…”
Section: Introductionmentioning
confidence: 52%
“…[61,75] It is widely accepted that their catalytic dyad forms an imidazoliumÀthiolate ion pair NH + /S À in the free enzyme (FE). [87] We demonstrated that the pK a values of the catalytic residues were controlled by the cooperative effect of the AS polar local environment (preoriented dipoles) and the free energy of solvation of the partially water exposed target catalytic group in the AS. The His-ImH + functions as a general acid, facilitating leaving group departure from the tetrahedral intermediate to produce an acylÀenzyme intermediate.…”
Section: Cysteine Protease Catalysis and Inhibitionmentioning
confidence: 87%
“…By applying our QM/SCRF(VS) molecular modeling approach (see below for some details about the method) [83] to simulate the enzyme AS on a QM molecular cluster, [84][85][86] we analyzed all possible protonation states of the catalytic dyad in free papain (FE) and its derivative (SSMe), in which the catalytic thiol was blocked by methylthiolation ( Figure 2). [87] We demonstrated that the pK a values of the catalytic residues were controlled by the cooperative effect of the AS polar local environment (preoriented dipoles) and the free energy of solvation of the partially water exposed target catalytic group in the AS. Based on our modeling simulations of all possible protonation states of the catalytic dyad, calculated versus ex-perimental pK a values, we suggested a novel structure for the catalytic Cys25-SH-His159-ImH + dyad in free papain at neutral pH, in which both residues were protonated, in contrast to the ion-pair paradigm.…”
Section: Cysteine Protease Catalysis and Inhibitionmentioning
confidence: 87%
See 2 more Smart Citations